Associations Between XPD Lys751Gln Polymorphism and Leukemia: A Meta-Analysis - Wen, Min; Zhou, Bo; Lin, Xin; Chen, Yunhua; Song, Jialei; Li, Yanmei; Zacksenhaus, Eldad; Ben-David, Yaacov; Hao, Xiaojiang (Frontiers in Genetics, 2018)
Objectives: The aim of the present study was to clarify the potential relationship of xeroderma pigmentosum group D (XPD) Lys751Gln polymorphisms and leukemia risk. Methods: Comprehensive electronic search in Pubmed, Web of Science, EBSCO, the Cochrane Library and China National Knowledge Infrastructure (CNKI) to find original articles about the association between XPD Lys751Gln polymorphisms and leukemia risk published before Mar 2017. Literature quality assessment was performed with the Newcastle-Ottawa Scale. Heterogeneity across studies was assessed using I2 statistics. Random- or fixed-effects models was used to calculate pooled odds ratios (ORs) in the presence or absence of heterogeneity, respectively. Sensitivity analyses to assess the influence of individual studies on the pooled estimate. Publication bias was investigated using funnel plots and Egger’s regression test. Analyses were performed by using Stata 14.0 and Revman 5.3. Results: Fourteen studies with a total of 7525 participants (2,757 patients and 4,768 controls) were included in this meta-analysis. We found that XPD Lys751Gln polymorphism significantly increased the risk of developing leukemia in both a dominant [Odds Ratio (OR)] = 1.21, 95%CI [1.10-1.35], P < 0.001) and heterozygote (OR = 1.22, 95%CI [1.09-1.36], P < 0.001) models. An allele model showed borderline significant increase in leukemia risk (OR = 1.13, 95%CI [1.00-1.27], P = 0.05). Subgroup analysis revealed a consistent association for some genetic models in Caucasian populations, adult or chronic groups, and in almost all models of childhood or acute groups. Conclusions: Our results overall indicate that XPD Lys751Gln polymorphism increases the risk of leukemia, especially in childhood and acute cases.